DIRECTIONS OF EMPLOYEE MANAGEMENT IN THE ENTERPRISE - Solijonov Mirfayozbek Shokirjon o‘g‘li; Alijonova Kumushxon Erkinboy qizi (Zeta Repository, 2023)
The essence of team management in industrial enterprises is to establish organizational-economic, socio-psychological and legal relations between employers, employees and other owners of the enterprise. These relations are based on the principles, methods and forms of influencing the behavior and activities of the interests of human resources in order to use them to the maximum.